Clinical researchAnomalous superficial palmar arch: a cadaveric study with clinical implications - Latiff, Azian A.; Othman, Faizah; Suhaimi, Farihah H.; Das, Srijit (Archives of Medical Science, 2008)
Introduction: The superficial palmar arch (SPA) is mainly formed by the ulnar artery with some contribution from the radial artery. As the name suggests, the SPA is arch shaped, but variation in its shape is not uncommon. Material and methods: The pattern of the SPA was observed on both sides of 25 upper limbs (n=50) of human cadavers in the Department of Anatomy. Results: We observed anomalous SPA in a single specimen. The SPA crossed superficial to the flexor retinaculum of the hand and, at a distance of approximately 2.5 cm from the flexor retinaculum, instead of taking an arched course, it traversed a straight course towards the digits. It gave off only two common palmar digital branches instead of the normal three digital branches. These two branches supplied the region between the third and fourth and the fourth and fifth digits respectively. The blood supply to the rest of the digits was from the branches of the radial artery. The radial artery did not give a superficial palmar branch to complete the superficial palmar arch. Conclusions: A knowledge of vascular anatomy and its pattern may be useful for graft surgeries, especially when the arteries of the upper limb are harvested for coronary artery grafts. Abnormal architecture of the palmar arch may be important for hand surgeons performing superficial dissections and the radiologists performing the angiographic procedures.